2011
DOI: 10.1103/physrevlett.106.034301
|View full text |Cite
|
Sign up to set email alerts
|

Blood Vessel Deformations on Microsecond Time Scales by Ultrasonic Cavitation

Abstract: Transient interactions among ultrasound, microbubbles, and microvessels were studied using high-speed photomicrography. We observed liquid jets, vessel distention (motion outward against the surrounding tissue), and vessel invagination (motion inward toward the lumen). Contrary to current paradigms, liquid jets were directed away from the nearest vessel wall and invagination exceeded distention. These observations provide insight into the mechanics of bubble-vessel interactions, which appear to depend qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
215
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(229 citation statements)
references
References 20 publications
13
215
0
1
Order By: Relevance
“…One may assume that the disruption occurs due to bubble growth and corresponding distension of the vessel wall. However, it was shown that most damage occurs as the bubble rapidly collapses and the vessel wall is bent inward or invaginated, causing high amplitude shear stress (27).…”
Section: Acoustic Cavitationmentioning
confidence: 99%
“…One may assume that the disruption occurs due to bubble growth and corresponding distension of the vessel wall. However, it was shown that most damage occurs as the bubble rapidly collapses and the vessel wall is bent inward or invaginated, causing high amplitude shear stress (27).…”
Section: Acoustic Cavitationmentioning
confidence: 99%
“…Microbubbles exert forces on the vessels to a much larger extend and can generate liquid microjets. 16 This IC behavior is more forceful and may increase BBB permeability to a larger extent. IC has been shown to be associated with microdamage to the cerebral vessels.…”
Section: Introductionmentioning
confidence: 99%
“…If microbubbles collapse near a blood vessel wall, the shock wave may create liquid jets that affect the vessel, creating holes in the vessel wall (38). Therefore, the expansion, oscillation and collapse of the bubbles and the resultant microstreaming, shock wave and fluid jets altogether result in microvessel distention, invagination and ultimately vessel rupture (12,18,20,29,38). …”
Section: Discussionmentioning
confidence: 99%
“…Although there are certain studies that have investigated microbubble parameters, including size or shell properties or ultrasound pulse parameters, including the fundamental transmission frequency, pulse repetition frequency, duty cycle, pulse length, mechanical index and acoustic peak negative acoustic pressure (8,(10)(11)(12)(13), these studies investigated few parameters simultaneously and did not investigate the different combinations of various levels of parameters. In addition, these studies focused only on the therapeutic effects of USMB, and seldom considered the damage to the skin induced by USMB.…”
Section: Introductionmentioning
confidence: 99%